Manajemen Pendidikan Inklusif SMA Muhammadiyah di Kota Yogyakarta - Witasoka, Dyah (PLD UIN Sunan Kalijaga, 2016)
This study is aimed at analyzing the activities of education management at the inclusive senior high schools affiliated to Muhammadiyah Foundation in Yogyakarta. The activities involved planning, implementation, and supervision in the curriculum and learning management, teachers and education personnels management, students management, facilities and infrastructure management, and budget management. This study was a phenomenology research with qualitative approach. This research results in three major findings. First, these inclusive high schools did not make any special planning in conducting an inclusive education. Second, these inclusive High school tried to manage activities based on the needs and characteristics of students with disabilities. Third, the school principals were involved directly in the implementation of inclusive education in their schools. Therefore, the school principals had a direct communication and interaction with the teachers, GPK (supporting) teachers, and the students with disabilities to monitor the inclusive service provided.[Penelitian ini bertujuan untuk mendeskripsikan kegiatan manajemen pendidikan pada SMA inklusif yang berada dalam naungan yayasan Muhammadiyah di Kota Yogyakarta. Kegiatannya mencakup perencanaan, pelaksanaan, dan pengawasan mulai dari manajemen kurikulum dan pembelajaran, manajemen pendidik dan tenaga kependidikan, manajemen peserta didik, manajemen sarana dan prasarana, serta manajemen pembiyaan.Penelitian ini merupakan penelitian fenomenologi dengan pendekatan kualitatif. Penelitian ini menghasilkan beberapa temuan utama. Pertama, SMA Inklusif tidak memiliki perencanaan khusus dalam menyelenggarakan pendidikan inklusif. Kedua, SMA Inklusif berusaha melaksanakan kegiatan manajemen sesuai dengan kebutuhan dan karakteristik siswa difabel. Ketiga, Kepala sekolah memiliki keterlibatan langsung dalam penyelenggaraan pendidikan inklusif di sekolahnya. Oleh karena itu, kepala sekolah melakukan komunikasi dan interaksi langsung dengan tenaga pendidik, tenaga GPK, bahkan siswa difabel agar dapat memantau pelayanan inklusif yang diberikan.]